Bioprospecção e caracterização de substâncias antifúngicas capazes de inibir espécies patogênicas de Cryptococcus a partir dos extratos de fungos endofíticos associados a plantas endêmicas de diferentes ecossistemas brasileiros - Cristiane Bigatti Pereira (2013)
Cryptococcosis is an opportunistic fungal disease that may affect healthy people. The disease is mainly caused by C. neoformans and C. gattii yeasts. The options of antifungal drugs available for the treatment are limited, so we search for new antifungal agents among the endophytic fungi (EF). Antifungal trial assays were performed by broth microdilution with 401 ethanolic endophytic fungi extracts isolated from six medicinal plants. The only isolated with constant antifungal activity was the UFMGCB 2032, identified as Mycosphaerella sp., obtained from the medicinal plant E. aff. bimarginata Berg., collected from Brazilian savannah. The fungal was grown on a large scale, the crude extract was submitted to partition with organic solvents, and the ethyl acetate fraction was fractionated by HPLC, which produced two secondary metabolites identified by mass spectra and NMR assays. The (6E, 12E)-2-amino-3,4-dihydroxy-2-(hydroxymethyl)-14-oxo-icosa-6,12-dienoic acid, compound 1, it was isolated by the first time and showed minimal inhibitory concentration (MIC) rate of 0.19-3.12 μg/mL. The second compound was the (6E)-2-amino-3,4-dihydroxy-2- (hydroxymethyl)-14-oxo-icosa-6-enoic acid, compound 2 or myriocin (MIC 0.19-0.78 μg/mL). The two isolated compounds showed antifungal activity against the Cryptococcus species isolates evaluated with MIC values similar to amphotericin B (AMB) MIC, and lower than fluconazole (FC) MIC values. The combined drugs assays indicate 25 % of synergism performed with compounds 1 and 2 combined with AMB and FC. The two compounds also exhibited activity against Candida albicans and C. krusei. The compounds 1 and 2 showed low cytotoxicity rate against MCF-7 and TK-10, and low inhibition percentage against Leishmania (Leishmania) amazonensis. Scanning electronic microscopy of the yeasts treated with isolated compounds permitted the observation of modification in yeasts shape (deformation) and cell wall modifications (depressions and additional wrinkles). Moreover, reduction in the C. gattii size and absence of budding cells yeasts after treatment was seen.